Chronic Atypical Depression as an Early Feature of Pituitary Adenoma: A Case Report and Literature Review - Cardoso, Filipa; Azizi, Heela; Kilpatrick, Alexander; Olayinka, Olaniyi; Khan, Tasmia; Kahn, Alexa; Canale, Cecilia; Ojimba, Chiedozie; Popoola, Olusegun; Nuthalapati, Deepa; Ahmad, Maleeha; Iskander, Mirna; et al. (Case Reports in Psychiatry, 2019)
Pituitary adenomas are often diagnosed as incidental findings on brain imaging. We present the case of a 52-year-old African American female patient with long standing depressed mood prior to the incidental finding of a pituitary adenoma. We explore the possibility of certain mood symptoms prompting an early diagnosis of pituitary adenoma.